2007
DOI: 10.1016/j.jtbi.2007.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Competing associations in bacterial warfare with two toxins

Abstract: Simple combinations of common competitive mechanisms can easily result in cyclic competitive dominance relationships between species. The topological features of such competitive networks allow for complex spatial coexistence patterns. We investigate selforganization and coexistence in a lattice model, describing the spatial population dynamics of competing bacterial strains. With increasing diffusion rate the community of the nine possible toxicity/resistance types undergoes two phase transitions. Below a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
(42 reference statements)
3
42
0
Order By: Relevance
“…In their model, however, a cooperator will necessarily invest somewhere, while in our case cooperators may remain dormant for long periods of time before eventually deciding to contribute to the common pool. In terms of potential implication of our findings, apart from their relevance for the successful evolution of prosocial behavior between selfish and unrelated individuals, from the biological point of view, the way inactive cooperators quarantine defectors and force them into convex isolated "bubbles" bears resemblance to the way the immune system works when trying to contain an infection [57]. We hope that this study will inspire future research aimed at investigating the role of conditional strategies in structured populations.…”
Section: Discussionmentioning
confidence: 74%
“…In their model, however, a cooperator will necessarily invest somewhere, while in our case cooperators may remain dormant for long periods of time before eventually deciding to contribute to the common pool. In terms of potential implication of our findings, apart from their relevance for the successful evolution of prosocial behavior between selfish and unrelated individuals, from the biological point of view, the way inactive cooperators quarantine defectors and force them into convex isolated "bubbles" bears resemblance to the way the immune system works when trying to contain an infection [57]. We hope that this study will inspire future research aimed at investigating the role of conditional strategies in structured populations.…”
Section: Discussionmentioning
confidence: 74%
“…Much work has been devoted to cyclic cases as for example the three-species cyclic game [21] or the corresponding game with four species where each species is preying on one other species while being at the same time the prey of another species [22][23][24][25][26][27][28][29]. Whereas some earlier papers have considered spatial and stochastic effects in systems with a larger number of species [30][31][32][33][34][35][36][37][38][39][40][41], it is only in the last few years that systematic theoretical studies of more complicated food networks with five or more species 2 have become available [19,[42][43][44][45][46][47][48][49][50][51][52][53][54]. One of the intriguing results of these studies has been the discovery of a rich variety of space-time patterns, including spirals where each wavefront is formed by a single species, fuzzy spirals due to the mixing of different species inside the waves, coarsening domains where every domain is formed by an alliance of mutually neutral species as well as coarsening processes where inside every domain spirals are formed, thus yielding non-trivial dynamics inside the coarsening domains [19,48,51,55].…”
Section: Introductionmentioning
confidence: 99%
“…In experiments with Escherichia coli, for example, it has been shown that arranging the bacteria on a Petri dish is crucial for keeping all three competing strains alive [8,36]. Accordingly, simulations of spatial rock-paper-scissors and related games of cyclic dominance have a long and fruitful history [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], which is firmly rooted in methods of statistical physics. In general, if the mobility in the population is sufficiently small [7], the spatial rock-paper-scissors game leads to the stable coexistence of all three competing strategies, whereby the coexistence is maintained by the spontaneous formation of complex spatial patterns.…”
Section: Introductionmentioning
confidence: 99%